Use of Geometric Mean in Bioequivalence Trials - Rasheed, Abdur; Siddiqui, Afaq Ahmed (International Journal of Statistics in Medical Research, 2015)
Bioequivalence data often do not follow the normality assumption on the linear (original) scale, therefore in that situation, the use of the logarithmic transformation is recommended. In the bioequivalence analysis, confusion arises about the use of geometric mean ratio when the logarithmic transformation is recommended by the regulatory authorities. The purpose of this research paper is to clear this confusion. Different average bioequivalence criteria are also reviewed in this paper.